A qualitative examination of the evolving role of sports technology in collegiate coaching - Brewer, Mollie; Childs, Kevin; Wilkins, Celeste; Smith, Zachary R.; Thomas, Spencer; Boyer, Kristy Elizabeth; Nichols, Jennifer A.; Beatty, Garrett F.; Ferris, Daniel P. (Frontiers in Sports and Active Living, 2025)
Coaches play a central role in shaping athlete performance and development. In collegiate sports, coaches must balance competitive goals with the broader needs of student-athletes. As technology becomes more available in sports, it is becoming increasingly embedded in the workflows and decision-making processes of coaching staff. While many recognize the growing presence of these tools in sports, there is limited understanding about how coaching staff select and integrate these tools into their professional practice. This study addresses this gap by investigating (1) the types of technologies that collegiate coaching staff use; (2) how coaches integrate those technologies into key coaching domains such as baseline testing, practice planning, and injury management; and (3) what motivates or hinders technology adoption in this environment. We conducted five semi-structured focus groups with 17 coaching staff members from National Collegiate Athletic Association (NCAA) Division I sports teams in the United States, representing men’s American football, men’s basketball, women’s basketball, women’s soccer, and women’s volleyball. Participants included coaches, athletic trainers, strength and conditioning staff, dietitians, sports scientists, and administrative staff. We provide an inventory of technologies in active use to support key aspects of coaching. Our findings show that when aligned with coaching goals, technology offers valuable support for decision-making, individualized student-athlete management, and coach-athlete communication. These findings also point to the importance of supporting coaching staff in managing the growing demands of technology use. By highlighting how collegiate coaching staff apply technology, this study deepens understanding of what technology integration in coaching looks like in real-world practice. The insights may offer valuable direction for scholars, coaches, and organizations who aim to strengthen coaching practice and athlete outcomes through thoughtful integration of technology.